Anfíbios e peixes são indicadores de diferentes hotpoints de biodiversidade na Mata Atlântica. - Covre, Amanda Caroline (2019)
The identification of consistent patterns of biodiversity that can be used to guide conservation actions has become one of the main objectives of Ecology. Therefore, the use of surrogate groups has highlighted in recent years. This approach is based on the assumption that the protection of a given taxon guarantees the safety of others in similar conditions, requiring less effort and /or financial investment. Its use is only feasible when the groups evaluated have high values of cross-taxon congruence and depends on the choice of well-known species, widely distributed and easily monitored. Considering that the presence of areas with high cross-taxon congruence between terrestrial and freshwater biodiversity has already been observed in tropical regions, it is possible for fish and amphibians to constitute good substitutes between them in the Atlantic Forest biome. Thus, we used geographic distribution data from bony fishes and amphibian species, as well as their functional characteristics throughout the biome, in order to evaluate the existence of cross-taxon congruence patterns and to identify if they are biodiversity surrogates. In this way we used spatial, morphological and ecological data were obtained from ichthyofauna and amphibiofauna for niche modelling of richness species and functional diversity, we used databases and bibliographical references; species presence / absence matrices were constructed; the functional diversity was calculated for the groups and the correlation between the values of richness and functional diversity of fish and amphibians was made through simple linear regressions. From the results it was verified that the highest values of fish richness and functional diversity are concentrated in the West Atlantic Forest, while those values for amphibians are located in the East. The regions of Serra do Mar and south of the Central Corridor were the only points that presented overlap between the groups. In this way, the obtained results offer valuable information that must be considered by the competent organs, responsible for the elaboration of strategies and plans of conservation and management of species.